Geographic disparities of dietary inflammatory index and its association with hypertension in middle-aged and elders in China: results from a nationwide cross-sectional study - Dong, Weihua; Man, Qingqing; Zhang, Jian; Liu, Zhen; Gong, Weiyi; Zhao, Liyun; Song, Pengkun; Ding, Gangqiang (Frontiers in Nutrition, 2024)
Background: Geographic distribution of dietary inflammatory index (DII) in China has not been thoroughly evaluated and evidence on the association between DII and hypertension among Chinese middle-aged and older population was inadequate. Objective：To investigate the geographic disparities of DII and its association with hypertension among Chinese middle-aged and elders. Methods：Data was from the China Adults Chronic Diseases and Nutrition Surveillance 2015 for middle-aged and older participants. DII was determined through a combination of 3 day 24-hour dietary recall interviews and a food frequency questionnaire. Spatial analysis was employed to investigate the geographic distribution of DII in China. Restricted cubic spline models and binary logistic regression analysis were used to assess the relationship between DII and hypertension. LASSO regression was applied for identifying key hypertension-related factors, with ROC and DCA ing built to evaluate its discriminatory power for hypertension. Results：A total of 52,087 middle-aged and older participants were included, among whom 36.6% had hypertension. it revealed that a clear spatial correlation in the national distribution of DII scores (Moran I: 0.252, P=0.001), with higher DII scores concentrated in the northwest and lower DII scores in the southeast. hypertensive participants had higher DII scores compared to those without hypertension (OR: 1.507 vs. 1.447, P=0.003). Restricted cubic spline models and binary logistic regression analysis demonstrated a positive association between DII and hypertension after adjusting for potential confounding factors. There was a significant increasing trend in the proportion of hypertensive individuals as DII scores increase (P for trend = 0.004). The nomogram model, constructed using key factors identified through LASSO regression, demonstrated a robust discriminative capacity, with an AUC of 73.2% (95% CI: 72.4%-74.0%). Decision curve analysis confirmed the reliability and effectiveness of the nomogram model. Conclusions：In Chinese middle-aged and elders, geographic disparities in dietary inflammatory potential are notable, with lower levels observed in the southeastern coastal regions and higher levels in the northwestern of China. Meanwhile, there is a positive association between the inflammatory potential of the diet and hypertension. Additional research is needed to investigate regional disparities in dietary inflammatory potential and pinpoint specific dietary patterns associated with lower inflammation.